Contribution of rotational diffusion to pulsed field gradient diffusion measurements. - Baldwin, A; Christodoulou, J; Barker, P; Dobson, C; Lippens, G (2007)
NMR diffusion experiments employing pulsed field gradients are well established as sensitive probes of the displacement of individual nuclear spins in a sample. Conventionally such measurements are used as a measure of translational diffusion, but here we demonstrate that under certain conditions rotational motion will contribute very significantly to the experimental data. This situation occurs when at least one spatial dimension of the species under study exceeds the root mean square displacement associated with translational diffusion, and leads to anomalously large apparent diffusion coefficients when conventional analytical procedures are employed. We show that in such a situation the effective diffusion coefficient is a function of the duration of the diffusion delay used, and that this dependence provides a means of characterizing the dimensions of the species under investigation.